Integrative Blockchain for Transparency and Efficiency of Carbon Trade Marketing Model in Bromo-Tengger-Semeru Region - Haryono, Haryono; Rahman, Arief; Zainal, Rifki Fahrial; Santoso, Bagus Teguh; Endarto, Budi (Westscience Press, 2025)
The integration of blockchain technology with Geographic Information Systems (GIS) offers an innovative solution for enhancing transparency and efficiency in carbon trade marketing. This study explores the development of an integrative blockchain-based carbon trade marketing model for the Bromo-Tengger-Semeru region, utilizing GIS analysis for spatial verification and dynamic monitoring of carbon stock. Results indicate significant carbon sequestration potential in the region, with high carbon stock zones and reforestation opportunities identified through GIS. The blockchain system improves transaction transparency, traceability, and efficiency through the use of smart contracts and decentralized ledgers. Stakeholder workshops demonstrated strong support for the proposed model, emphasizing its potential to overcome existing challenges in carbon trading. The integration of GIS and blockchain ensures spatial accuracy and enhances stakeholder confidence, making it a viable approach for scaling carbon trade initiatives. This study contributes to the advancement of sustainable carbon trade practices, offering a replicable model for other regions.